2020
DOI: 10.14260/jemds/2020/126
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Wild Animal Related Injuries in the Sub Himalayan Terrain of North Bengal

Abstract: A B S T R A C T BACKGROUNDWild animal related injury is a serious health problem for people living in the foothills of the sub Himalayan terrain. Geographically the foothills are proximal to the tea gardens and the dense forests which in turn are in close proximity to human habitation. Thus, the tea garden workers and labourers as well as others are always at imminent threat from the abundant wildlife. The type of injury could be quite serious, sometimes grotesque and even life threatening. Though we regularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Human deaths generally occur when villagers are trying to defend their crops or property or due to accidental encounters, but also sometimes when elephants attempt to search homes for food (Naha, Sathyakumar, Dash, Chettri, & Rawat, 2019). A study in North Bengal suggested that elephants were responsible for 80% of human medical cases due to HWC (Samaddar, Bagchi-Samaddar, Roy, & Das, 2020). Often in retaliation for the losses due to conflict (Gureja, Menon, Sarkar, & Kyarong, 2007), at least 100 elephants are killed annually by people (Rangarajan et al, 2010), though again documentation problems suggest this might be an undercount (Naha et al, 2019).…”
Section: Study Area and Study Speciesmentioning
confidence: 99%
“…Human deaths generally occur when villagers are trying to defend their crops or property or due to accidental encounters, but also sometimes when elephants attempt to search homes for food (Naha, Sathyakumar, Dash, Chettri, & Rawat, 2019). A study in North Bengal suggested that elephants were responsible for 80% of human medical cases due to HWC (Samaddar, Bagchi-Samaddar, Roy, & Das, 2020). Often in retaliation for the losses due to conflict (Gureja, Menon, Sarkar, & Kyarong, 2007), at least 100 elephants are killed annually by people (Rangarajan et al, 2010), though again documentation problems suggest this might be an undercount (Naha et al, 2019).…”
Section: Study Area and Study Speciesmentioning
confidence: 99%